La fraternidad y sus debilidades - Duque, João (2021)
The discourse on fraternity, in the different fields of its application from politics to religion, often uses the notion as if it had a clear and univocal meaning. However, it is a category loaded with different, even problematic, meanings. The article starts with a brief critique of the abstract and very generic use of this category, and focuses on the analysis of a significant number of problems of the concrete fraternal relationship. From this recourse, a notion of fraternity that is both open and concrete, which finds the brother (sister) in every vulnerable human being, is gained. A pedagogy of the fraternal relationship as a relationship open to every human being, in the concrete reality of face to face, is a pedagogy on the way to a true universal fraternity, beyond abstract or uniform globalism, and beyond closed tribalism.